Comparative Outcomes of Catheter-Directed Thrombolysis Plus Anticoagulation Versus Anticoagulation Alone in the Treatment of Inferior Vena Caval Thrombosis. (February 2015) - Alkhouli, Mohamad; Zack, Chad J.; Zhao, Huaqing; Shafi, Irfan; Bashir, Riyaz
Abstract : Background—: The contemporary practice patterns and role of catheter-directed thrombolysis (CDT) in the treatment of inferior vena cava thrombosis is unknown. Methods and Results—: The Nationwide Inpatient Sample database was used to identify patients with a principal discharge diagnosis of inferior vena cava thrombosis ( International Classification of Diseases - Ninth Revision -Clinical Modification, 453.2) from 2005 to 2011. We compared patients treated with CDT plus anticoagulation with patients treated with anticoagulation alone. We used propensity scores to construct 2 matched groups of 563 patients for comparative outcomes analysis. Among 2674 patients admitted with inferior vena cava thrombosis, 718 (26.9%) underwent CDT. The national CDT utilization rates increased from 16.0% in 2005 to 34.7% in 2011 ( P <0.001). Based on the propensity-matched comparison, the inhospital mortality was not significantly different between the CDT and the anticoagulation groups (2.0% versus 1.4%; P =0.49). The rates of pulmonary embolism (12.1% versus 7.8%; P =0.02), intracranial hemorrhage (1.6% versus 0.2%; P =0.03), and acute renal failure (13.9% versus 9.4%; P =0.02) were significantly higher in the CDT group. The CDT group had longer length of stay and higher hospital charges compared with the anticoagulation group. Conclusions—: There has been a steady increase in the use of CDT in the treatment of patients with inferior vena cava thrombosis in the United States. This observational study showed no significant difference in mortality between CDT versus anticoagulation alone; however, the bleeding events and resource utilization were higher in the CDT group. Adequately powered randomized controlled trials are needed in this area. Abstract : Supplemental Digital Content is available in the text.